Proficiency, Psychological Wellbeing, and Coping of the College Freshmen of the University of Nueva Caceres - Maria Marietta B. Basbas (Journal of Public Health Sciences, 2023)
The transition to college is one of the significant life adjustments. Students are expected to adapt to this new environment. However, difficulties in school adaptation may result in social, emotional, and learning instability. This quantitative descriptive survey research determined the skills proficiency, psychological well-being and coping strategies of the University of Nueva Caceres first-year college students for the school year 2021– 2022. The study participants consisted of 429 first-year students of the University of Nueva Caceres. The Skills Profiler Test, Ryff's Scales of Psychological Well-being (SPWB), and Brief-COPE Inventory were used to measure the variables. The Statistical Package for the Social Sciences (SPSS) was used to analyze the data. The results indicated that the first-year college students of UNC have a skills gap in math, reasoning, and vocabulary. They reflect positive well-being that may help them pursue college life and obstacles that may come their way. The results further suggest that there is a need for the university to come up with programs or interventions that will develop the first-year students' critical thinking skills to succeed in mathematics and life.